(untitled) (The Planet, 2024)
Introduction: The study of carcinoma of the breast, a prevalent malignancy affecting women worldwide, is crucial for advancing medical knowledge and improving patient outcomes. This study aims to explore the various clinical presentations, risk factors, and histopathological features associated with breast carcinoma. Methods & Materials: This descriptive, cross-sectional study was conducted over one year from January 2023 to December 2023 at a tertiary care hospital in a rural area to assess the clinico-pathological characteristics of carcinoma breast among female patients. The study included 50 female patients diagnosed with carcinoma breast. Data were entered into a database and analyzed using statistical software (SPSS version 26.0). Results: In a study of 50 breast carcinoma patients, 60% of cases occurred in the left breast and 40% in the right. The most common symptom was a breast lump (50%), followed by lumps with ulceration (20%), pain (12%), axillary swelling (8%), and skin fixation (4%). Nipple retraction was observed in 40% of cases, and the upper outer quadrant was the most frequently involved area (62%). Tumor sizes were predominantly T2 (46%), with 36% of patients showing no palpable axillary lymph nodes. FNAC diagnosed 95.3% as malignant with 100% specificity and 95.3% sensitivity. Histopathological analysis found 100% of poorly differentiated tumors had positive lymph node involvement, compared to 70% of moderately and 50% of well-differentiated tumors. Conclusion: This study underscores a predominance of late-stage diagnosis, with many patients presenting with advanced disease, highlighting the need for early detection strategies.